Influence of medical shortage on GP burnout: a cross-sectional study. (3rd September 2018) - Picquendar, Guillaume; Guedon, Antoine; Moulinet, Fanny; Schuers, Matthieu
Abstract: Background: Burnout is a common occurrence among GPs, decreasing quality of and access to care and impacting both physician and patient health. The link between burnout and low medical density has never been studied. Objectives: This study aimed to assess the prevalence of burnout and its related factors, including low medical density, among GPs. Method: We conducted a cross-sectional survey. A self-administered questionnaire was sent to all of the 1632 GPs in Normandy, France, in September 2015. The Maslach Burnout Inventory was used to assess the three burnout dimensions: emotional exhaustion (EE), depersonalization (DP) and low personal accomplishment (PA). Results: In all, 501 GPs sent back their questionnaire (response rate: 30.7%); 487 questionnaires were analysed. Burnout had been experienced by 43.3% of the physicians in the sample. Nearly 24% of the respondents scored high EE, 27.3% scored high DP, and 13.3% scored low PA. Low medical density [odds ratios (OR): 2.16 (1.31–3.54)], and intent to quit [OR: 4.40 (2.59–7.47)] were strongly linked to the three burnout dimensions. Burnout was not linked with quantitative workload. Conclusion: Burnout among GPs was common. Low medical density and intent to quit were strong predictors of burnout. Given the current medical demographic crisis, these results highlight the relationship between burnout and medical shortage. Qualitative workload may have a more significant influence on burnout than quantitative workload. Recruiting more GPs is necessary, but may prove insufficient in fighting burnout. Preventive and curative actions are required, especially in areas with low medical density.